Analisis Pemilihan Supplier Kayu Dengan Pendekatan Vendor Performance Indicator (VPI) Dan Metode Analytical Hierarchy Process (AHP) - Luailyus Alhaqy; Hana Catur Wahyuni (Metode : Jurnal Teknik Industri, 2023)
PT Romi Violeta is one of the manufacturing companies engaged in the furniture manufacturing industry. The observation results show that there are discrepancies in the quantity and quality of raw materials originating from supplier shipments. On the other hand, companies are faced with determining supplier priorities to meet the needs of company orders. Based on this. Analysis is needed in supplier selection. Vendor Performance Indicator (VPI) is an approach that will measure problems related to standards, quality of raw materials, delivery time. To assist the Vendor Performance Indicator (VPI) approach in the ranking process in selecting the best supplier based on a series of calculation stages, the Analytical Hierarchy Process (AHP) method will be used. The results of this study found that there are 10 Vendor Performance Indicators in supplier selection. The first priority in supplier selection is quality criteria with a weight of (0.422) and the lowest is flexibility with a weight value of (0.054), UD. Prajawari is the best supplier with a total weight value of (0.548), The second priority is UD. Randu Muria with a weight of (0.261), the last priority is UD. Trijaya with a weight of (0.191).